The Effect of Promotion and Price on Consumer Purchase Decisions - Nobertus Notaris Laoli; Otanius Laia; Yuterlin Zalukhu; Sophia M. Kakisina (Manunggal Halim Jaya, 2024)
This research aims to analyze the influence of promotion and price on consumer purchase decisions at PT. Arken Ehowu Putra Motor Kota Gunungsitoli. The main objectives of this study are to determine whether there is a significant influence of promotion on purchase decisions, the influence of price on purchase decisions, and the simultaneous influence of promotion and price on consumer purchase decisions. Based on the coefficient of determination test results, an R-Square value of 0.495 or 49.5% indicates that the promotion variable (X1) has a strong influence on consumer purchase decisions (Y). Additionally, the Adjusted R-Square value of 0.506 shows that the promotion and price variables (X2) collectively influence consumer purchase decisions by 50.6%. The F-test results, with a significance value of 0.000 < 0.05 and an F-value of 13.853 > 3.67, indicate that H3 is accepted, meaning there is a significant influence of variables promotion and price on consumer purchase.